Fusel Alcohols of Wine – Alternative Nitrogenous Substance in Alcoholic Fermentation - Paata Vashakidze; Marine Bezhuashvili (Current Topics in Agricultural Sciences Vol. 8, 2022)
The materials of European-style wine created from Georgian native Rkatsiteli varieties have been investigated. The addition of nitrogenous compounds, such as diammonium phosphate (DAP) and alternative nitrogen substance (ANS), causes alcoholic fermentation of grape juice. Higher alcohols are identified by a strong, pungent smell and taste and can have a significant effect on the sensorial quality and character of wine and brandy Higher alcohol and residual sugar concentrations in produced wine materials have been researched in response to the following factors: The concentration of alternative nitrogen substance, temperature of alcoholic fermentation and titratable acidity, for the experiment have been used wine materials fermented by the natural microflora, strains of cultural yeast Sacch. Vini - kakhuri 42, Sacch. Vini - Rkatsiteli 61 and dry yeast B 2000. Significantly lower concentrations of higher alcohols (fusel oils) produced in the fermentation of grape juice by natural microflora, pure yeast cultures, and dry yeast have been discovered as significant favorable impacts of alternative nitrogenous substance (ANS).